2004
DOI: 10.1128/jvi.78.11.5805-5811.2004
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Endogenous Retrovirus Transmission Characteristics of Galactose α1-3 Galactose-Deficient Pig Cells

Abstract: Galactose ␣1-3 galactose (Gal) trisaccharides are present on the surface of wild-type pig cells, as well as on viruses particles produced from such cells. The recognition of Gal sugars by natural anti-Gal antibodies (NAb) in human and Old World primate serum can cause the lysis of the particles via complement-dependent mechanisms and has therefore been proposed as an important antiviral mechanism. Recently, pigs have been generated that possess disrupted galactosyl-transferase (GGTA1) genes. The cells of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…For some viruses, including porcine endogenous retrovirus, pseudorabies virus, and lymphocytic choriomeningitis virus, neutralization by nonimmune human serum is triggered by natural antibodies binding to Gal␣1-3Gal epitopes on virus (21,37,43,47,50). However, we previously reported that naturally occurring antibodies to Gal␣1-3Gal are not involved in neutralizing HSV-1 virus (12).…”
Section: Discussionmentioning
confidence: 99%
“…For some viruses, including porcine endogenous retrovirus, pseudorabies virus, and lymphocytic choriomeningitis virus, neutralization by nonimmune human serum is triggered by natural antibodies binding to Gal␣1-3Gal epitopes on virus (21,37,43,47,50). However, we previously reported that naturally occurring antibodies to Gal␣1-3Gal are not involved in neutralizing HSV-1 virus (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, when retroviruses bud from the surfaces of cells from transgenic pigs expressing human complement regulator proteins, the viruses acquire numerous cellular proteins, including these human complement regulatory proteins. Expression of these proteins on the virus surface will also prevent the human immune system from eliminating the virus (235,260,316), increasing the risk of transmission. Without the human complement regulator genes on the surface of PERV, antiGal-alpha-1,3-Gal antibodies prevent virus infection (207,208).…”
Section: Use Of Transgenic Pigs To Overcome Immunological Rejectionmentioning
confidence: 99%
“…Complement sensitivity of VSV harvested from pig cells with or without ␣-Gal epitope. To confirm that virus inactivation by human serum is mainly mediated by ␣-Gal epitope and anti-␣-Gal natural antibodies, we employed the porcine testis cell line ST-IOWA and its derivative (ST-IOWA Gal-null) lacking the ␣-galactosyl transferase gene (GGTA1) (37). While Galnull cells have been shown to produce PERV resistant to human serum (37), VSV passaged through these cells was tested in this study.…”
Section: Fig 2 Demonstration Of Hcd55 Incorporation On Vsv Particlesmentioning
confidence: 99%
“…To confirm that virus inactivation by human serum is mainly mediated by ␣-Gal epitope and anti-␣-Gal natural antibodies, we employed the porcine testis cell line ST-IOWA and its derivative (ST-IOWA Gal-null) lacking the ␣-galactosyl transferase gene (GGTA1) (37). While Galnull cells have been shown to produce PERV resistant to human serum (37), VSV passaged through these cells was tested in this study. ST-IOWA Gal-null cells produced VSV resistant to complement-mediated inactivation, although at the highest serum concentration (50%) there was some degree of inactivation, implying that although ␣-Gal is the major xenoreactive epitope, there are other minor xenoreactive epitopes (9).…”
Section: Fig 2 Demonstration Of Hcd55 Incorporation On Vsv Particlesmentioning
confidence: 99%